Factors affecting social misconduct amongst adolescents in Melaka Tengah district - M Jamsiah,; H Hazlinda, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2009)
Background : Social misconduct amongst adolescents is a worrying and ever growing problem in Malaysia, despite efforts taken to overcome it. Methods : A cross sectional study was conducted among secondary school students in Melaka Tengah District to measure the prevalence and determine the factors associated with social misconduct amongst adolescents. A total of 414 form four students were recruited by systematic random sampling fulfilling the study criteria between Jun to September 2008, from eight randomly selected secondary schools in the district. Data were collected using a structured self-administered questionnaire and analyzed using SPSS software version 12.0. Socio-demographic, housing and family factors in relation with social misconduct were studied. Results : The prevalence of the social misconduct in this study was 70.5%. The most prevalent misconduct includes loitering (37.4%), truancy (30.0%), watching pornographic films (28.7%), and involved in pre-sexual activities (23.7%). The factors that showed significant association with social misconduct were sex and race. Conclusion : The prevalence of social misconduct is high among adolescent and males as well as Malays are at higher risk. Activities planned for adolescents should be stressed on the danger and effects of social misconduct and be more focused towards male and Malay adolescents.